Effect of the Program «Caring for caretakers»: Findings of a multicenter study (Colombia Medica, 2024)
Objective: To assess the effectiveness of the program Caring for the Caregivers on the caring ability of family caregivers of people with chronic illnesses attended by programs coordinated by the Latin American nodes for the care of caregivers with chronically ill family members.Methods: The study had a Quasi-experimental method with an experimental group (family caregivers that took the Program Caring for the caregivers and a control group. Data was collected with the Ngozi Nkongho’s Caring Ability Inventory (CAI). The sample was taken by convenience in (8) nodes, with an average of 60-100 family caregivers for a total group of 643 individuals (417 in the experimental group and 226 in the control group). Statistical tests were used to evaluate proposals of normality and the Mann-Whitney U test to evaluate data. Results: Findings report similar study groups with small differences in ages and socioeconomic levels. Family caregivers that took part in the Program significantly improved their caring ability with improvement in each of the dimensions of the caring ability. Discussion: The effectiveness of the Program Caring for the caregivers in the caring ability of family caregivers is a significant finding that match with previous reports and it confirm the importance of having specific proposals for the care of caregivers in the Latin American context. Findings shows a strengthening of the general caring ability of family caregivers, as well as an straightening of each one of their dimensions that is favorable to the Program effect. These findings slightly differ from previous findings because in previous studies the caring ability never showed increase in all its components.